Comparison between 18F-FDG PET/MRI and MDCT for the assessment of preoperative staging and resectability of gastric cancer. Issue 6 (June 2016) - Lee, Dong Ho; Kim, Se Hyung; Joo, Ijin; Hur, Bo Yun; Han, Joon Koo
Abstract: Purpose: To investigate if 18F-FDG PET/MRI can improve the diagnostic performance of TNM staging and help make an accurate decision for resectability in patients with gastric cancer compared to MDCT. Materials and methods: Forty-two patients with histologically confirmed gastric cancers underwent preoperative MDCT and 18F-FDG PET/MRI. M-staging and resectability was assessed in all patients, and T- and N-staging was evaluated in 30 of 42 patients who underwent curative gastrectomy. Two abdominal radiologists independently assessed their MDCT images and 18F-FDG PET/MRI and determined preoperative TNM staging and resectability of gastric cancers. Diagnostic performance with MDCT and 18F-FDG PET/MRI were compared using McNemar's test and receiver operating characteristic analysis. Results: Diagnostic accuracies for T and N staging were not significantly different between MDCT and 18F-FDG PET/MRI in both readers. However, 18F-FDG PET/MRI showed significantly improved diagnostic accuracy for M staging in one reader (P = 0.008) and marginal improvement in the other reader (P = 0.063) compared to MDCT. Regarding the resectability of gastric cancers, diagnostic accuracy (92.9% for both readers) of 18F-FDG PET/MRI was significantly higher than that (76.2% for reader 1 and 64.3% for reader 2) of MDCT in both readers (P < 0.05). Conclusion: 18F-FDG PET/MRI may improve diagnostic accuracy for preoperative M staging as well as resectability of gastric cancers compared to MDCT.